Analysis of the Effects of Cryofrequency on Localized Fat - Froes Meyer, Patrícia (J Clin Aesthet Dermatol, 2020)
BACKGROUND: Cryofrequency combines cryotherapy with radiofrequency, reaching the tissue in different layers, providing various biological effects, and reducing localized adiposity. OBJECTIVE: We sought to evaluate the efficacy of cryofrequency in reducing localized adiposity. METHODS: The study population consisted of 63 women with infra-abdominal adiposity, evaluated before and after treatment using evaluation protocols, questionnaires, and ultrasound imaging. The volunteers were randomly distributed into three subgroups; of these, Group 1 (G01) received the cryofrequency treatment (temperature of −10°C, 85% power); Group 2 (G02) underwent cryofrequency associated with ultracavitation (frequency of 60 Hz, 70% power, shooting at 25%, duty cycle of 60% on and 40% off); and the control group (CG) received cryotherapy alone (temperature of −10°C). All groups were submitted to four treatment sessions, one session per week. RESULTS: The reduction in the fat layer analyzed by ultrasonography showed that the right side of G01 presented a significant difference in comparison with CG (p=0.01); a significant difference was also observed in the comparison between the G01 and G02 groups (p=0.001). Considering the left side, significant differences were observed in G01 when compared with CG (p=0.01) and between G01 and G02 (p=0.001). The variables of plicometry and perimetry presented a significant difference relative to in CG; however, no differences were observed with regard to weight or body mass index (p>0.05). The majority of participants reported positive feelings about the treatment. CONCLUSIONS: The cryofrequency protocol alone led to a significant reduction in the fat layer but its association with ultracavitation led to superior results.